Factors affecting the acceptance of mobile commerce in Pakistan - Rind, Muhammad Malook; Shah, Asadullah (IIUM Press, International Islamic University Malaysia, 2017)
Information and Communication Technology (ICT) tools have enabled traditional bricks-and-mortar businesses into electronic business (E-businesses) and also Mobile Commerce (Mcommerce). In recent past M-commerce has emerged and set new trends in commerce and business market. M-commerce has become attractive choice for consumers and retailers to facilitate and conduct business activities through mobile handheld devices. M-commerce usage in developed countries such as USA, UK, Australia and other technologically advanced countries has been accepted at large scale. However, Mcommerce still seems to take very slow pace in developing economies such as Pakistan, where its acceptance is quite low. The aim of this study is to investigate and identify the significant factors that affect consumers’ ‘behavioural intention’ to accept M-commerce in Pakistan. A model is proposed in this research to measure ‘behavioural intention’ to use M-commerce in Pakistan. In this research, variables such as Perceived Usefulness (PU), Perceived Ease of Use (PEOU), Trust, Cost, Risk, Compatibility, Social Influence and Facilitating Conditions are measured. The proposed research model was validated through Structural Equation Modeling (SEM) using Analysis of Moment Structures (AMOS) software. A total of 414 responses were collected using clustered sampling approach. Each variable is measured on seven point Likert scale. Research findings indicate that eleven out of thirteen hypotheses were found to be statistically significant. Moreover, PU, Risk, Cost, Trust and PEOU are the most significant factors that influence the behavioural intention to accept M-commerce, respectively.